Mechanism of action of non-coding RNAs and traditional Chinese medicine in myocardial fibrosis: Focus on the TGF-β/Smad signaling pathway - Li, Chunjun; Meng, Xiangxiang; Wang, Lina; Dai, Xia (Frontiers in Pharmacology, 2023)
Heart failure (HF) is a serious public health problem worldwide, and cardiac fibrosis can lead to the excessive deposition of cardiac fibroblasts and then accelerate the progression of HF. Numerous researches have shown that the TGF-β/Smad signaling pathway plays a key role in the progression of cardiac fibrosis. Therefore, targeted inhibition of the TGF-β/Smad signaling pathway could be a potential therapeutic measure for cardiac fibrosis. Currently, as the researches on non-coding RNAs (ncRNAs) move forward, a variety of ncRNAs targeting TGF-β and its downstream Smad proteins are paid much attention. Besides, Traditional Chinese Medicine (TCM) has been widely used in China for the treatment of cardiac fibrosis. As more and more molecular mechanisms of natural products, herbal formulas, and proprietary Chinese medicines are revealed, TCM has been proven to act on cardiac fibrosis by modulating multiple targets and signaling pathways, especially the TGF-β/Smad signaling pathway. Therefore, this work focuses on the TGFβ/Smad signaling pathway, summarizes the role of TGF-β/Smad classical and non-classical signaling pathways in the cardiac fibrosis, and discusses the recent research advances in ncRNAs targeting the TGF-β/Smad signaling pathway and TCM against cardiac fibrosis, with a view to providing new insights into the prevention and treatment of cardiac fibrosis.